Assessing public awareness on the potential health risks of phthalate exposure in plastic consumer products - Hu, Andy; Chen, Dale; BCIT School of Health Sciences, Environmental Health (BCIT Environmental Public Health Journal, 2021)
Phthalates are chemical agents used to improve the plasticity of plastic products. Their ubiquitous use in various commercial products results in extensive exposure to humans. Toxicological studies have linked phthalate exposure to developmental and reproductive toxicity, presenting potential health risks. This study investigated the general population on their knowledge and hazard perception of phthalate exposure. The assessment determined if changes in policies or guidelines are needed to minimize potential health impacts from improper plastics handling.